(untitled) (Research, Society and Development, 2021)
Hospital environment has factors that promote increased infections caused by microorganisms allowing them to remain viable for long periods on surfaces and fomites. The aim of our study was to identify the viability of Candida albicans in hospital environment common surfaces with biological fluids presence and disinfectants. Four surfaces (cotton fabric, synthetic fabric, egg crate foam mattress and, ceramic floor) were contaminated with a strain of Candida albicans ATCC 26790 and with an association of distilled water, blood, saliva and urine. Also, combinations of surfaces and fluids with addition of 70% alcohol and 2% sodium hypochlorite were tested. Viability was identified at 1, 3, 7, 14 and 21 days by Colony Forming Units counting. C. albicans presented 14 days viability in hospitals fabrics with absence of liquids and maintained this persistence under influence of distilled water and blood. It also showed low growth with urine addition and there was growth inhibition with 2% sodium hypochlorite while with 70% alcohol and blood there was persistence for up to 7 days in synthetic fabric and mattress. The understanding of these yeasts persistence in hospital surfaces and fomites is essential for a better delineation of protocols control the spread and these infections prevention in healthcare environments.